Geometric non-linear structural analysis by spline finite element method - Shi, Ping. (2009)
The development presented in this thesis is geometrically non-linear analysis using the C1-spline finite elements. The formulation is based on the general geometrically non-linear strain-displacement relations derived from Novozhilov's theory. It is well known that a serious drawback of C degree elements is their exposure of the shear locking phenomenon. The present development can remove this restriction for non-linear structural analysis by finite element method.